"We Are All Indigenous!" Insurgent Universality on the Extractive Frontier. Issue 3 (3rd July 2022) - Wilson, Japhy
ABSTRACT: This paper tells the inside story of a spontaneous uprising in the Ecuadorian Amazon in 2017, in which mestizo, Afro-descendant and Indigenous workers and communities confronted the combined forces of a multinational oil company and a militarized state. The paper documents a rapidly evolving battle that achieved a remarkable victory, and bears witness to the fleeting emergence of an insurgent form of political universality. It suggests that the decolonial dichotomy between top-down universalism and a bottom-up pluriverse should be replaced by an approach that is attentive to manifestations of universality performed by subaltern subjects in their confrontations with extractive capital.